QLearning based business differentiating routing mechanism in SDN architecture - Zijin JIN; Julong LAN; Yiming JIANG; Penghao SUN; Peng WEI (网络与信息安全学报)
With the diversified development of the current network,users’ demand grows as well which brings great challenge for its load ability.A QLearning based business differentiating routing mechanism in SDN architecture was proposed to guarantee users’ routing QoS.To do that,four modules (discovery of link,classification of link,intensive learning and Q-value table sending) were designed to assign different paths to data streams of different attributes.The experiment shows that the proposed algorithm can decrease the packet loss rate to less than 5% and for some of the data streams,this rate is almost 0,simultaneously,it also helps the delay problem.